Differential Localization of Chemotactic Signaling Arrays during the Lifecycle of Vibrio parahaemolyticus - Heering, Jan; Ringgaard, Simon (Frontiers in Microbiology, 2016)
When encountering new environments or changes to their external milieu, bacteria use elaborate mechanisms to respond accordingly. Here we describe how Vibrio parahaemolyticus coordinates two such mechanisms – differentiation and chemotaxis. V. parahaemolyticus differentiates between two distinct cell types: short rod-shaped swimmer cells and highly elongated swarmer cells. We show that the intracellular organization of chemotactic signaling arrays changes according to the differentiation state. In swimmer cells chemotaxis arrays are strictly polarly localized, but in swarmer cells arrays form both at the cell poles and at irregular intervals along the entire cell length. Furthermore, the formation of lateral arrays increases with cell length of swarmer cells. Occurrence of lateral signaling arrays is not simply a consequence of the elongated state of swarmer cells, but is instead differentiation state-specific. Moreover, our data suggest that swarmer cells employ two distinct mechanisms for localization of polar and lateral signaling arrays, respectively. Furthermore, cells show a distinct differentiation and localization pattern of chemosensory arrays, depending on their location within swarm colonies, which likely allows for the organism to simultaneously swarm across surfaces while sustaining a pool of swimmers immediately capable of exploring new liquid surroundings.